Microstructure evolution of semisolid billet of nano-sized SiCp/7075 aluminum matrix composite during partial remelting process. (15th April 2016) - Jiang, Jufu; Wang, Ying; Nie, Xi; Xiao, Guanfei
Abstract: Microstructure evolution of the nano-sized SiCp /7075 composite during partial remelting process was investigated. The results show the microstructure of the semisolid billet fabricated by rheoforming the semisolid slurry consisted of fine near spheroids and equiaxed grains. Existence and uniform distribution of nano-sized SiC particles have been illustrated by using X-ray diffraction, high resolution scanning electron microscopy and transmission electron microscopy. Grain size of the semisolid billet during the partial remelting process firstly increases and then is followed by a decrease with increasing remelting temperature. Average grain sizes of the semisolid billet upon remelting temperatures of 580 °C, 590 °C, 600 °C and 610 °C are 32.4 μm, 36.3 μm, 37.5 μm and 35.3 μm, respectively. A coarsening trend of solid grain upon soaking for different time at 600 °C was found in the microstructure. When the soaking time increases from 0 min to 25 min, the average grain size increases from 25 μm to 41.7 μm. Coarsening tends to occur via Ostwald ripening and coalescence. A lower coarsening rate constant of 40.5 μm 3 ·s − 1 is achieved due to hindering action of nano-sized SiC particles to coarsening of solid grains. Graphical abstract: Highlights: Microstructure evolution of remelted SiCp /7075 nanocomposite was studied. Grain size firstly increased and then decreased with elevated temperature. Grain coarsening of remelted nanocomposite occurred with increasing soaking time. Ostwald ripening and coalescence led to grain coarsening during isothermal holding.